Let's go through each step of your prompt.
-
Identify like terms. The like terms in the expression \(-2.1x + 3.7 + 5 + 4.9x\) are:
- \( -2.1x\) and \( 4.9x\) (these are the terms with \(x\))
- \(3.7\) and \(5\) (these are the constant terms)
-
Rewrite using properties of operations when necessary. We can rearrange it using the commutative property: \[ -2.1x + 4.9x + 3.7 + 5 \] Applying the distributive property is unnecessary here, but we can prepare it as follows: \[ (-2.1 + 4.9)x + (3.7 + 5) \]
-
Simplify. Simplify the coefficients: \[ (-2.1 + 4.9)x = 2.8x \] And for the constant terms: \[ (3.7 + 5) = 8.7 \] So now we combine them to give: \[ 2.8x + 8.7 \]
-
Check by substitution. Let's evaluate both forms with \(x = 1\).
-
For the original expression: \[ -2.1(1) + 3.7 = -2.1 + 3.7 = 1.6 \] \[ 5 + 4.9(1) = 5 + 4.9 = 9.9 \] Sum: \[ 1.6 + 9.9 = 11.5 \]
-
For the simplified expression: \[ 2.8(1) + 8.7 = 2.8 + 8.7 = 11.5 \]
-
Since both calculations yield \(11.5\), the original expression and the simplified expression are equivalent.
Thus, the correct expression is indeed: \[ \boxed{2.8x + 8.7} \]